Simulating the formation of massive seed black holes in the early Universe - II. Impact of rate coefficient uncertainties - Glover, Simon (Monthly notices of the Royal Astronomical Society, 2015)
We investigate how uncertainties in the chemical and cooling rate coefficients relevant for a metal-free gas influence our ability to determine the critical ultraviolet field strength required to suppress H2 cooling in high-redshift atomic cooling haloes. The suppression of H2 cooling is a necessary prerequisite for the gas to undergo direct collapse and form an intermediate mass black hole. These black holes can then act as seeds for the growth of the supermassive black holes (SMBHs) observed at redshifts z ∼ 6. The viability of this model for SMBH formation depends on the critical ultraviolet field strength, Jcrit: if this is too large, then too few seeds will form to explain the observed number density of SMBHs. We show in this paper that there are five key chemical reactions whose rate coefficients are uncertain enough to significantly affect Jcrit. The most important of these is the collisional ionization of hydrogen by collisions with other hydrogen atoms, as the rate for this process is very poorly constrained at the low energies relevant for direct collapse. The total uncertainty introduced into Jcrit by this and the other four reactions could in the worst case approach a factor of five. We also show that the use of outdated or inappropriate values for the rates of some chemical reactions in previous studies of the direct collapse mechanism may have significantly affected the values of Jcrit determined by these studies.
Gesehen am 11.08.2021